Cardiovascular reactivity in real life settings: Measurement, mechanisms and meaning - Zanstra, Ydwine Jieldouw (2010)
Cardiovascular reactivity to stress is most commonly studied in the laboratory. Laboratory stressors may have limited ecological validity due to the many constraints, operating in controlled environments. This paper will focus on paradigms that involve the measurement of cardiovascular reactions to stress in real life using ambulatory monitors. Probably the most commonly used paradigm in this field is to measure the response to a specific real life stressor, such as sitting an exam or public speaking. A more general approach has been to derive a measure of CV variability testing the hypothesis that more reactive participants will have more variable heart rate or blood pressure. Alternatively, self-reports of the participants’ perceived stress, emotion or demands may be linked to simultaneously collected ambulatory measures of cardiovascular parameters. This paper examines the following four questions: (1) What is the form and what are the determinants of stress-induced CV reactivity in real life? (2) What are the psychophysiological processes underlying heart rate and blood pressure reactivity in real life? (3) Does CV reactivity determined in the laboratory predict CV reactivity in real life? (4) Are ambulatory cardiovascular measures predictive of cardiovascular disease? It is concluded that the hemodynamic processes that underlie the blood pressure response can reliably be measured in real life and the psychophysiological relationships seen in the laboratory have been obtained in real life as well. Studies examining the effects of specific real life stressors show that responses obtained in real life are often larger than those obtained in the laboratory. Subjective ratings of stress, emotion and cognitive determinants of real life stress (e.g. demand, reward and control) also relate to real life CV responses. Surprisingly, ambulatory studies on real life cardiovascular reactivity to stress as a predictor of cardiovascular disease are rare. Measuring the CV response to stress in real life may provide a better measure of the stress-related process that are hypothesized to cause disease than is possible in the laboratory. In addressing these questions, below we review the studies that we believe are representative of the field. Therefore, this review is not comprehensive.